Particle formation with supercritical fluids : challenges and limitations - Turk, Michael (Supercritical fluid science and technology, 2014)
Particle formation with supercritical fluids is a promising alternative to conventional precipitation processes as it allows the reduction of particle size and control of morphology and particle size distribution without degradation or contamination of the product. The book comprehensively examines the current status of research and development and provides perspectives and insights on promising future directions. The introduction to high pressure and high temperature phase equilibria and nucleation phenomena provides the basic principles of the underlying physical and chemical phenomena, allowing the reader an understanding of the relationship between process conditions and particle characteristics. Bridging the gap between theory and application, the book imparts the scientific and engineering fundamentals for innovative particle formation processes. The interdisciplinary "modus operandi" will encourage cooperation between scientists and researchers from different but complementary disciplines.